2021
DOI: 10.3168/jds.2020-19195
|View full text |Cite
|
Sign up to set email alerts
|

Milk losses and dynamics during perturbations in dairy cows differ with parity and lactation stage

Abstract: Milk yield dynamics during perturbations reflect how cows respond to challenges. This study investigated the characteristics of 62,406 perturbations from 16,604 lactation curves of dairy cows milked with an automated milking system at 50 Belgian, Dutch, and English farms. The unperturbed lactation curve representing the theoretical milk yield dynamics was estimated with an iterative procedure fitting a model on the daily milk yield data that was not part of a perturbation. Perturbations were defined as periods… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 38 publications
0
25
1
Order By: Relevance
“…Previous work showed that mastitis influences the lactation curves, and therefore classical lactation models including the entire time series cannot be used as such (Andersen et al, 2011). Several authors have recently developed methodologies that predict the unperturbed milk yield trajectory of a cow (Adriaens et al, 2020(Adriaens et al, , 2021Poppe et al, 2020;Ben Abdelkrim et al, 2021), from which the residuals can be used to quantify deviations. The methodology that we developed previously has the advantage of being applicable for QMY trajectories too, which allowed us to use an similar method at both the cow and the quarter level in this study.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous work showed that mastitis influences the lactation curves, and therefore classical lactation models including the entire time series cannot be used as such (Andersen et al, 2011). Several authors have recently developed methodologies that predict the unperturbed milk yield trajectory of a cow (Adriaens et al, 2020(Adriaens et al, , 2021Poppe et al, 2020;Ben Abdelkrim et al, 2021), from which the residuals can be used to quantify deviations. The methodology that we developed previously has the advantage of being applicable for QMY trajectories too, which allowed us to use an similar method at both the cow and the quarter level in this study.…”
Section: Methodsmentioning
confidence: 99%
“…To calculate milk losses as the expected versus the actual milk production, first a reliable estimation of the expected production must be obtained. For the CMY analysis, the method described in Adriaens et al (2021) was used. This is based on an iterative fitting of the Wood model (Wood, 1967) in which records that are part of a perturbation are removed to obtain a fit unaffected by perturbations.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations